Reaction kinetics and the development and operation of catalytic processes : proceedings of the 3rd international symposium, Oostende (Belgium), April 22-25, 2001 /: proceedings of the 3rd international symposium, Oostende (Belgium), April 22-25, 2001. (2001) - Unknown
No abstract available